Radiosensitive and Radioresistant Phases in the Antibody Response - Frank J. Dixon; David W. Talmage; Paul H. Maurer (1952)
Summary and Conclusions The initial antibody response of rabbits to I131 labelled bovine gamma globulin (I*BGG) appears to consist of a brief, radiosensitive phase followed by a radioresistant phase which lasts for the duration of the response. The specific anamnestic response is radioresistant, indicating that the initial contact with the antigen leaves a lasting impression which obviates the radiosensitive phase. The exact nature of the first phase is not apparent. It seems possible, however, that this phase is concerned with a specific adaptation of the gamma globulin synthesizing mechanism to the antigen. If this occurs, the modification of the mechanism is apparently retained even after appreciable amounts of antibody cease to be produced.